Intimate Partner Violence, Psychopathy, and Recidivism: Do Psychopathic Traits Differentiate First-time Offenders from Repeated Offenders? - Cunha, Olga Cecília Soares da (2022)
The current study analyzes the relation between psychopathic traits and the four facets of psychopathy (i.e., interpersonal, affective, lifestyle, and antisocial) and general and intimate partner violence (IPV) recidivism. The Psychopathy Checklist-Revised (PCL-R) and the Marital Violence Inventory (IVC) were completed by a sample of 279 male perpetrators of IPV who were retrospectively classified as general repeated offenders versus first-time offenders and IPV repeatedoffenders versus IPV first-time offenders. Four separate binary logistic regression analyses were conducted controlling for age and criminal and abuse variables. PCL-R total scores and the antisocial facet were positively correlated with general repeated offenses, despite criminal history showing higher associations with general recidivism. For IPV repeated offenders, PCL-R antisocial facet and criminal history were statistically significant, being the last one the variable that presents higher association with IPV recidivism. These results support the role of criminal history as an important variable for repeated offenses.